Synthesis and Characterization of TiO2 Nanoparticles Doping on Cellulose as Adsorbent for Removal of Rhodamine B in Aqueous Solution - Allwar Allwar; Mayla Nur Fatima; Bayu Wiyantoko (EKSAKTA: Journal of Sciences and Data Analysis, 2021)
Cellulose from banana fruit bunch was used as a precursor for doping titanium oxide (TiO2) in producing of TiO2/cellulose adsorbent.  Cellulose was obtained by chemical impregnation using potassium hydroxide (KOH) and followed by the hydrothermal process at 250oC for 5 h. The mixture of TiO2 nanoparticles and cellulose was carried out into hydrothermal reactor under de-ionized water and ethanol and heated up to 200oC for 4 h in graphite furnace. Surface morphology analysis showed that the TiO2 clearly immobilized on the surface of cellulose with an increasing roughness of surface and irregular size of porosity. The development of the amorphous to the crystalline phase of TiO2/cellulose was clearly observed by the XRD. The effectiveness of TiO2/cellulose for removal of rhodamine B was investigated from different parameters of adsorption in aqueous solution. Kinetic models were well described by the pseudo-first and second-order with the best correlation coefficient (R2) attributing to the occurrence of chemisorption and physisorption mechanism.